Current Mental Distress Among Men With a History of Radical Prostatectomy and Related Adverse Correlates. Issue 5 (September 2020) - Ilie, Gabriela; White, Joshua; Mason, Ross; Rendon, Ricardo; Bailly, Greg; Lawen, Joseph; Bowes, David; Patil, Nikhilesh; Wilke, Derek; MacDonald, Cody; Rutledge, Robert; Bell, David
Recent reviews and observational studies have reported that patients with prostate cancer (PCa) are at increased risk of mental health issues, which in turn negatively affects oncological outcomes. Here, we examine possible explanatory variables of mental distress in a population-based cohort of men who have undergone radical prostatectomy (RP). Data were derived from a Maritimes-Canada online survey assessing patient-reported quality of life outcomes between 2017 and 2019 administered to 136 men (47–88 years old, currently in a relationship) who have undergone RP for their PCa diagnosis. The primary outcome was a validated assessment of mental distress, the Kessler Psychological Distress Scale (K10). Urinary function was assessed using the International Prostate Symptom Score, and relationship satisfaction was assessed using the Dyadic Assessment Scale. A multivariate logistic regression assessed the contribution of urinary function, relationship satisfaction, age, multimorbidity, additional treatments, medication for depression and/or anxiety, and survivorship time. A total of 16.2% men in this sample screened positive for mental distress. The severity of urinary problems was positively associated with increased mental distress ( OR = 4.79, 95% CI [1.04, 22.03]), while increased age ( OR = 0.87, 95% CI [0.78, 0.97]), relationship satisfaction ( OR = 0.14, 95% CI [0.3, .077]), and current medication for anxiety, depression, or both ( OR = 0.09, 95% CI [0.02, 0.62]) were protective factors. Survivorship time, the presence of additional comorbidities, or PCa treatments were not identified to be statistically significant contributions to the fitted model. Here, we report that RP survivors are prone to presenting with increased mental distress long after treatment. Screening for mental distress during RP survivorship is recommended.